2014
DOI: 10.1523/jneurosci.3261-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Partial Loss of Presenilin Impairs Age-Dependent Neuronal Survival in the Cerebral Cortex

Abstract: Mutations in the presenilin (PSEN1 and PSEN2) genes are linked to familial Alzheimer's disease (AD) and cause loss of its essential function. Complete inactivation of presenilins in excitatory neurons of the adult mouse cerebral cortex results in progressive memory impairment and age-dependent neurodegeneration, recapitulating key features of AD. In this study, we examine the effects of varying presenilin dosage on cortical neuron survival by generating presenilin-1 conditional knock-out (PS1 cKO) mice carryin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 40 publications
4
44
0
Order By: Relevance
“…Previous work has shown that PS2 expression is up-regulated in the absence of PS1 (Watanabe et al, 2014), which may compensate for behavioral and synaptic deficits caused by PS1 deficiency. We therefore examined the impact of the L435F mutation on behavioral and synaptic phenotypes in a Psen2−/− background.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has shown that PS2 expression is up-regulated in the absence of PS1 (Watanabe et al, 2014), which may compensate for behavioral and synaptic deficits caused by PS1 deficiency. We therefore examined the impact of the L435F mutation on behavioral and synaptic phenotypes in a Psen2−/− background.…”
Section: Resultsmentioning
confidence: 99%
“…Further analysis of Psen conditional knockout mice with varying Psen2 gene dosage showed that partial inactivation of PS also results in age-dependent neurodegeneration, though with lesser severity and a later age of onset (Watanabe et al, 2014). To examine the impact of the L435F mutation on neuronal survival, relative to the Psen1 wild-type allele, we generated Psen1 F/L435F ; Psen2 −/− ; Camk2a-Cre mice and littermate Psen1 F/+ ; Psen2 −/− ; Camk2a-Cre and Psen1 F/F ; Psen2 −/− mice.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, we crossed Psen1 L435F KI mice to the Psen2 −/− background to enable more direct and accurate analysis of the phenotypic effects of the L435F mutation on PS1 function (Xia et al, 2015). Indeed, we previously found that loss of PS1 expression leads to up-regulation of PS2 expression (Watanabe et al, 2014), which would mask the effects of PS1 loss-of-function mutations. Curiously, Veugelen et al don’t object to the converse approach of overexpressing PSEN1 and APP .…”
Section: Discussionmentioning
confidence: 99%
“…Evidence also suggests the regulation of the transcription factor EGR-1 may be regulated by APP, which may play a role in AD development and memory formation [265]. Mutations in NRF1 targets PSEN1 and PSEN2 may also lead to the development of neurodegenerative disease [266,267,268]. In addition PSEN1 and PSEN2 transcription, expression, promoter activity, and mRNA levels are influenced by the PARKIN protein [269].…”
Section: Mechanisms Of Actions Of Estrogenic Endocrine Disruptors mentioning
confidence: 99%